2002
DOI: 10.1055/s-2002-35612
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Neonatal Leukemoid Reaction and Bronchopulmonary Dysplasia in Low-Birth-Weight Infants: A Cross-Sectional Study

Abstract: Leukemoid reaction in low-birth-weight (LBW) infants is a rare, recently documented phenomenon, implicated in the sequence of multiorgan inflammatory diseases of preterm infants. The aim of the present paper is to establish whether a neonatal leukemoid reaction is related to bronchopulmonary dysplasia (BPD) development in LBW infants. The design was a case-controlled, retrospective study of all premature infants (born Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
(40 reference statements)
1
20
0
3
Order By: Relevance
“…Our study provides further support to the findings of previous research showing an association between elevated WBC and BPD 14,16 in premature infants exposed, and unexposed, to histological chorioamnionitis. Hsiao and Omar 16 showed an increased risk of BPD with total WBC >30 000 per mm 3 , in infants of 1000 g birth weight.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study provides further support to the findings of previous research showing an association between elevated WBC and BPD 14,16 in premature infants exposed, and unexposed, to histological chorioamnionitis. Hsiao and Omar 16 showed an increased risk of BPD with total WBC >30 000 per mm 3 , in infants of 1000 g birth weight.…”
Section: Discussionsupporting
confidence: 91%
“…Our data support other research, indicating an association between BPD and leukocytosis in preterm infants. [14][15][16] To our knowledge, this is the first study limited to infants exposed to histological chorioamnionitis, and is the first report of an increase in survival with an associated leukocytosis.…”
Section: Discussionmentioning
confidence: 82%
“…The terms leukocytosis or leukemoid reaction have been used to describe an abnormally elevated white blood cell (WBC) count. Hill and Duncan 1 used a threshold of WBC count >50 000 to define leukocytosis, whereas Zanardo et al 2 used a cutoff of 40 000. Others used absolute neutrophil count values for defining pathology, for example, a count of >10 standard deviations above the mean for a given gestational age or an absolute neutrophil count of >30 000 during the first week after birth for diagnosing neutrophilia.…”
Section: Introductionmentioning
confidence: 99%
“…7,16 An association between fetal inflammatory response syndrome and neonatal morbidities, especially chronic lung disease has been reported in small case series and case-control studies. 2,7,13 However, its association with other neonatal morbidities is not known.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Neonatal LR has been described in a number of case reports in association with various clinical conditions including prematurity, chromosomal anomalies, exposure to antenatal corticosteroids (ANS), severe anemia, infections, and bronchopulmonary dysplasia (BPD). 8,9,[13][14][15][16][17][18][19][20] In the recent clinical studies by Calhoun et al 10 and Rastogi et al, 21 LR occurred in 1.3% to 15% of infants admitted to neonatal intensive care units, with no significant association demonstrated between LR and maternal and neonatal variables. In addition, Zanardo et al, 20 in a retrospective case-controlled study of preterm infants with gesta-tional age of Ͻ32 weeks, showed that BPD was associated with higher incidence of LR (5 of 50 vs 0 of 50; P ϭ .001).…”
mentioning
confidence: 99%